More than 100 years of a mistake: on the anatomy of the atlas of the enigmatic Macrauchenia patachonica - Püschel, Hans P. (2023)
Ever since the discovery of the first remains of Macrauchenia patachonica by Charles Darwin in 1834, this taxon has puzzled researchers with its peculiar anatomy. Being the best-known member of the family Macraucheniidae and with fossil records in extensive areas of South America between the Middle to Late Pleistocene/earliest Holocene, M. patachonica has been extensively studied over decades, and recently even included in molecular studies. However, there are some elements of its skeleton that have been inadvertently unstudied. One of these elements is the atlas of M. patachonica, that due to a misidentification made 159 years ago by the prominent zoologist Hermann Burmeister, was not examined or illustrated by later researchers even with access to excellent specimens. Here, we describe and illustrate the atlas of M. patachonica for the first time, correcting Burmeister’s mistake. Overall, the anatomy of the atlas of M. patachonica is consistent with the anatomy of older macraucheniids. The atlas described by Burmeister as being M. patachonica probably corresponds to that of a bovid. It is noteworthy that most mounted skeletons of M. patachonica present today in museum exhibitions, display a correct atlas derived from a more complete specimen discovered ca. 1904 by the prominent palaeontologist Santiago Roth.